If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 3n + -5 = 7n + 11 Reorder the terms: -5 + 3n = 7n + 11 Reorder the terms: -5 + 3n = 11 + 7n Solving -5 + 3n = 11 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. -5 + 3n + -7n = 11 + 7n + -7n Combine like terms: 3n + -7n = -4n -5 + -4n = 11 + 7n + -7n Combine like terms: 7n + -7n = 0 -5 + -4n = 11 + 0 -5 + -4n = 11 Add '5' to each side of the equation. -5 + 5 + -4n = 11 + 5 Combine like terms: -5 + 5 = 0 0 + -4n = 11 + 5 -4n = 11 + 5 Combine like terms: 11 + 5 = 16 -4n = 16 Divide each side by '-4'. n = -4 Simplifying n = -4

| 9x+2.3=10.3 | | 11x+4=-29 | | 8x+115=71 | | 6x+6=4x+32 | | 8r-20=4 | | 4x+13=61 | | 7x-7=42 | | 5-.25x=11 | | 7x-5.8=13.1 | | 10x-3=-83 | | 23j-26=89 | | 8x-3.2=37.6 | | 12x-10=-130 | | 12x+7=139 | | -5-5(2-p)=-5 | | 20n-2=138 | | 3x-8=55 | | 5p-21=-1+p | | 5x+10=9x | | 3x+36=9x-14 | | -4+9x=8 | | 7(2+3)=2z+4 | | 5x+10=-7x+1 | | 8(4k+-4)=-5k-32 | | 1.4x-0.9x+0.7=-2.2 | | 7(z+3)=2z+4 | | 5x+7=3x+19 | | -8(-8x+-6)=-6x-22 | | (13x+9)=(15x-1) | | 8(-7x-4)=32 | | 3(m-7)=-3 | | 2(x+3)-1=x-14 | | 5x-17=3x+14 | | 1.5+24=3-46 | | 1.5x+24=3x-46 | | 3t+44=50 | | -4y+2+5y=3y-15 | | 3(5p-3)=5(p-1) | | 12+0.35x=20.05 | | 15x+21=6x+7 | | 5p+6=-4p-8 | | 6q-1=-q+20 | | X+7=6x-3 | | 16=6x-7 | | -2m+13=2m-3 | | 7x+12-11x=44 | | 18+7x=(-9) | | 8x+10=11x+3 | | 8-5(x+3)=13 | | 6+3x=39 | | 5x-9=2(x+3) | | -2=3X+10 | | -(3b-15)=6(2b+5) | | 7j+3=24 | | 3.9w-17.9=-2.3 | | 50=3t-4 | | 5x+9=39 | | 8(x+6)-9=x-10 | | 4X=7-11 | | .4n+.1=.5(n+4) | | 5=2g+y | | 6t-8=154 | | 5+-4=6 | | k+1=3k-1 | | a+(a-3)=(a+4)-(a+1) |